THE ROLE OF PAREMIAS IN LANGUAGE AND CULTURE - Khudaybergenova Gulbakhor (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation  This  article  examines  the  role  of  paremias,  such  as  proverbs, sayings,  and  idioms,  in  both  the  Uzbek  and  English  languages,  focusing  on  their linguistic and cultural significance. Paremias are short, fixed expressions that convey cultural  wisdom,  moral  lessons,  and  social  norms.  Through  a  comparison  of  both languages, the article explores how these expressions reflect the values, traditions, and worldviews of their respective societies. The study highlights the linguistic features of paremias, their function in communication, and their cultural importance in shaping societal norms and reinforcing social values. The research also emphasizes the role of paremias as tools for communication, providing succinct, culturally rich expressions that reflect the worldview of different communities.